VISUALISASI DATA SENSOR PADA SISTEM PEMANTAUAN SUHU DAN KELEMBABAN RUANGAN BERBASIS ANTARMUKA WEB - Qisthi Alhazmi Hidayaturrohman; Prasetyo Yuliantoro; Reda Rizal (Bina Teknika, 2020)
The internet of things technology has become one technology that plays a role in the industrial revolution 4.0. Not only limited to the data communication between devices over internet protocol communication data networks, but on the IoT device is also need the proper interface to visualize the sensor data which has received by the server node, and with that result, the user can understand easily and get insight from those data which has an exchange or communicate each other on the system. In the previous research by Yuliantoro, et. al., the IoT device was designed only to communicate to other devices, where the web server as a server node was designed to receive the sensor data. The design of the visualize system in this research, designed by the PHP script and web server which is connected to the NodeMCU in a wireless local area network or WLAN. The sensor data from NodeMCU sent to the server, then the result will be shown visually by the website interface. Based on the results of this study, the visualized data has been shown the full sensor data, with the delay is following the delay of the NodeMCU, 60 seconds.